Online information seeking behavior for cancer related disease: A developed and developing country comparison - Saleh, Nurliyana; Kartiwi, Mira; Gunawan, Teddy Surya (IEEE Explore, 2018)
With the rapid development of information and communication technology, seeking information over the internet has been time efficient and easily available regardless of time and place. The channels that provide information through internet have improvised and grown broader. The ubiquity of internet and availability of information has caused people to acquire information about health easily for their respective purposes. In this study, examination of information seeking behaviour through search engine for cancer related disease from developed and developing country was conducted, using Malaysia and Singapore as case studies. The content analysis technique is used to analyse the information seeking behaviour about cancer related disease. The findings show that there are differences in the pattern of information seeking behaviour between those from developed and developing nations.